2019
DOI: 10.24297/jaa.v10i0.8425
|View full text |Cite
|
Sign up to set email alerts
|

Virulence and Antimicrobial Characteristics of Escherichia Coli Isolated from Diseased Chickens in China and Algeria

Abstract: To reveal and compare the prevalence of pathotypes and virulence genes, as well as antimicrobial resistance and genotyping of poultry E. coli isolates from China and Algeria. Pathotype and seven virulence genes were tested by PCR, susceptibility to antimicrobials was evaluated using broth microdilution method, and genotyping was analyzed by PFGE. Six isolates were identified as pathogenic E. coli. Virulence gene testing showed that the frequency of ompT, iss, fimC, iroN, hlyF and iutA was high in the isolates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(16 reference statements)
1
1
0
Order By: Relevance
“…Indeed, except for one E. coli strain, which was positive for the stx2 gene detected at one Mostaganem farm, all the isolates were negative for the major genes encoding VFs. This finding is in accordance with previous Algerian studies describing a low prevalence of stx genes in E. coli isolates from poultry origin, i.e., a recent Algerian study showed the presence of stx2 in only one E. coli isolate from broiler chickens, which had just died [35]. Another study conducted in the north of Algeria revealed the total absence of the stx2 gene and the presence of the stx1 gene in only two E. coli strains isolated from diarrheic hens and chickens [36].…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, except for one E. coli strain, which was positive for the stx2 gene detected at one Mostaganem farm, all the isolates were negative for the major genes encoding VFs. This finding is in accordance with previous Algerian studies describing a low prevalence of stx genes in E. coli isolates from poultry origin, i.e., a recent Algerian study showed the presence of stx2 in only one E. coli isolate from broiler chickens, which had just died [35]. Another study conducted in the north of Algeria revealed the total absence of the stx2 gene and the presence of the stx1 gene in only two E. coli strains isolated from diarrheic hens and chickens [36].…”
Section: Discussionsupporting
confidence: 92%
“…Azam et al claimed that the majority of E. coli strains isolated from dead chickens showed resistance to ampicillin (98.6%), tetracycline (97.3%), and ciprofloxacin (72%) [29]. An equally high resistance prevalence was confirmed in various studies conducted on different continents [30] (Tab. 6).…”
Section: Discussionmentioning
confidence: 92%